Effects of spirulina platensis addition on performance, immune response, hematological, selected bacteria activity and rumen morphology of lambs - Abdulrahman S. Alharthi; Hani H. Al-Baadani; Ahmed A. Alghonaim; Maged A. Al‑Garadi; Abdullah N. Alowaimer; Ibrahim A. Alhidary (Italian Journal of Animal Science)
The aim of this study is to investigate the effects of different levels of Spirulina platensis in the diet on performance, immune response, hematological, activity of selected bacteria and rumen morphology of lambs. Forty-eight weaned lambs (aged 3 months) were used and then divided into four groups with 6 pens per group (2 lambs/pen), including a control group and three groups fed pelleted complete feed containing 0.20%, 0.40% and 0.80% spirulina powder, respectively. The study lasted 70 days, during which all target parameters were assessed and analysed. The results showed that spirulina powder had a positive effect on body weight and daily weight gain of lambs on days 42–70 and 1–70 (p < 0.05). Daily feed intake was also increased by spirulina powder (p < 0.05). The T2 and T3 had a higher white blood cell count (35 and 70 days) (p < 0.05). The percentage of granulocytes increased at T3 (35 days) and T2 (70 days), while lymphocytes at T3 (35 and 70 days) and monocytes at T1 and T2 (35 days) were decreased (p < 0.05). Red blood cell counts and percent haematocrit were lower at T1 (35 days), T1 and T3 (70 days) (p < 0.05). IL-2 in T3 (35 and 70 days), IL-4 in T1 (35 days) and IL-10 in the spirulina groups (70 days) were higher (p < 0.05). Butyrivibrio fibrisolvens was higher in the T2 and T3 groups and lower in the T1 group (p < 0.05). In addition, Ruminocoocus Albus, Ruminococcus Flavefaciens and Streptococcus Bovis were higher in the Spirulina groups (p < 0.05). Papilla height (T2), papilla area, density and total papilla area (T2 and T3) were increased (p < 0.05). In conclusion, the results suggest that lambs fed Spirulina platensis had higher weight gain and feed intake, white blood cell count and IL-2, IL-4, and IL-10 levels, rumen microbiota, papilla height, density, and total papilla surface area compared to the control group, with most parameters tending to be higher in dose. Nevertheless, further studies are needed to elucidate the specific mechanisms and to determine the most effective and safest dose of Spirulina platensis for lambs.